2003
DOI: 10.1029/2002jd002497
|View full text |Cite
|
Sign up to set email alerts
|

Columnar aerosol single‐scattering albedo and phase function retrieved from sky radiance over the ocean: Measurements of Saharan dust

Abstract: [1] The single-scattering albedo and phase function of African mineral dust are retrieved at 14 wavelengths across the visible spectrum from ground-based measurements of the aerosol optical thickness and the sky radiance taken in the solar principal plane. The retrieval algorithm employs the radiative transfer equation to solve by iteration for these properties that best reproduce the observed sky radiance, and is therefore independent of particle shape. The estimated error in the retrieved single-scattering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 76 publications
8
33
0
Order By: Relevance
“…At λ=530 nm the SSA specified by Cattrall et al (2003) is about 0.96±0.2 in good agreement with our results. By comparing their and others retrieval results with SSA model results based on laboratory data of the complex refractive indices of bulk minerals they found that the remotely sensed values result in a significantly weaker dust absorption than model predictions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…At λ=530 nm the SSA specified by Cattrall et al (2003) is about 0.96±0.2 in good agreement with our results. By comparing their and others retrieval results with SSA model results based on laboratory data of the complex refractive indices of bulk minerals they found that the remotely sensed values result in a significantly weaker dust absorption than model predictions.…”
Section: Discussionsupporting
confidence: 81%
“…Retrievals of remote sensing data by Cattrall et al (2003) from Saharan dust passages at Dry Tortugas, Florida revealed SSA values across the visible spectral range. At λ=530 nm the SSA specified by Cattrall et al (2003) is about 0.96±0.2 in good agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we wish to study the effect of maximum particle size in a dust size distribution on optical properties and forcing in order to simulate the cut-off problem. In this context we would like to note that independent remote sensing techniques, e.g., to derive micro-physical particle properties from radiometric radiation measurements at the ground surface (Dubovik et al, 2002), may lead to SSA in the visible range, which is significantly larger than dust SSA calculated with in-situ data (Cattrall et al, 2003). Obviously, current retrievals of dust properties have certain inaccuracies as recently demonstrated by Müller et al (2010).…”
Section: Introductionmentioning
confidence: 92%
“…Phys. from Saharan desert regions at 550 nm yielded a value of 0.97 ± 0.02 (Cattrall et al, 2003). Additionally, the wind roses in Figure 8 MSE is a key parameter that can be used to estimate the radiative forcing effects due to 15 atmospheric particles on global climate.…”
Section: Resultsmentioning
confidence: 99%